2005
DOI: 10.1007/bf02844013
|View full text |Cite
|
Sign up to set email alerts
|

Human perceptions of artificial surfaces for field hockey

Abstract: Measuring the performance of a sports surface is typically derived from a series of field and laboratory tests that assess the playing properties under simulated game conditions. However, from a player's perspective their own comfort and confidence in the surface and its playing characteristics are equally if not more important. To date no comparative study to measure playing preference tests has been made. The aim of this research was to develop a suitable method for eliciting player perceptions of field hock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 11 publications
2
17
0
7
Order By: Relevance
“…Players' perceptions of the courts inform their response to mechanical differences between surfaces (Milani et al, 1997), therefore measuring perceptions can provide an insight into how tennis players differentiate between court surfaces (Fleming et al, 2005). Similar to previous reports (Lockhart, Woldstad, Smith, & Ramsey, 2002;Stiles & Dixon, 2007), this study revealed differences in perception of the two tennis courts, which corresponded to differences in mechanical data.…”
Section: Player Perceptions Of Tennis Courtssupporting
confidence: 81%
See 3 more Smart Citations
“…Players' perceptions of the courts inform their response to mechanical differences between surfaces (Milani et al, 1997), therefore measuring perceptions can provide an insight into how tennis players differentiate between court surfaces (Fleming et al, 2005). Similar to previous reports (Lockhart, Woldstad, Smith, & Ramsey, 2002;Stiles & Dixon, 2007), this study revealed differences in perception of the two tennis courts, which corresponded to differences in mechanical data.…”
Section: Player Perceptions Of Tennis Courtssupporting
confidence: 81%
“…Therefore, perceptions may reveal associations with biomechanical variables associated with increased injury risk. Measuring perception provides further information regarding players' experience of the surface which can not only supplement mechanical measures but also aid in the development of new mechanical tests (Fleming et al, 2005). This study identified differences in players' perceptions of their ability to perform tasks such as sliding and changing direction between court surfaces which could influence their biomechanical response.…”
Section: Player Perceptions Of Tennis Courtsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanics of players' motion and the pace of the game are different depending on what surface is used [97]. An analysis of field hockey players' subjective opinions during an intensive match on both an indoor surface and on artificial turf indicates that the latter is characterized by higher degree of hard ness, which in turn led to an overall faster game play caused by higher ball rebounds [98][99][100]. It was also es tablished that synthetic turf led to a higher frequency of acute injuries, which primarily resulted from the in creased pace of the game [101], modified equipment, e.g.…”
Section: Injuriesmentioning
confidence: 99%